A descriptive catalogue of Daniells work in the Victoria Memorial - Ray, Nisith Ranjan, 1911-; Daniell, Thomas, 1749-1840; Daniell, William, 1769-1837 (Victoria Memorial, 1976)
Catalog of paintings by Thomas Daniell, 1749-1840, and William Daniell, 1769-1837, British painters.